Kesesuaian Lahan untuk Tembakau di Madura dengan Menggunakan Sistem Informasi Geografis - Firman Farid Muhsoni (Lambung Mangkurat University Press, 2010)
Rainfed area causes utilization of Madura’s land less optimum. Theaim of this research is to make a map of agroecosystem that potentially inagriculture by using remote sensing, crop model development is based on thecondition of land physically. The method of this research is by classifying theland conformity for crop by checking off the quality of land for every unit of land.The results of this research are a potential map of tobacco cultivation 51.971 ha(11.4%) is appropriate, 8.749 ha (1.9%) is very appropriate. The developmentof rainfed area that appropriate for Madura area for jepon kenik tobacco varietywith age of harvest is short (86 days) and crop indice is high (580.0).